2013
DOI: 10.1271/bbb.130033
|View full text |Cite
|
Sign up to set email alerts
|

Lower Photostability of Capsanthin Dispersed in an Aqueous Solution

Abstract: Food-additive grades of capsanthin, lutein, lycopene, and -carotene dispersed in aqueous solutions were photo-irradiated using a Xenon weather meter, and the levels of carotenoids were measured by HPLC and the absorbance method. Capsanthin photo-degraded more rapidly than the carotenoids tested, with less oxygen consumption. Unlike carotenes, capsanthin was partially converted into analogous colored compounds during degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Te reduction of a * and ASTA values may be due to the oxidative degradation of capsanthin and capsorubin by light, temperature, humidity, and other factors [37,38]. Capsanthin and capsorubin may react with active oxygen to promote the breaking of their conjugated double bonds, resulting in epoxides and peroxides that cause the discoloration of peppers [15,39,40], while capsanthin could be transformed into orange or yellow pigments in the process of photodegradation, such as zeaxanthin, lutein, β-carotene, and other carotenoid substances [41,42]. Moreover, the oxidative degradation process of yellow carotenoids is relatively slow [6].…”
Section: Color Traitsmentioning
confidence: 99%
“…Te reduction of a * and ASTA values may be due to the oxidative degradation of capsanthin and capsorubin by light, temperature, humidity, and other factors [37,38]. Capsanthin and capsorubin may react with active oxygen to promote the breaking of their conjugated double bonds, resulting in epoxides and peroxides that cause the discoloration of peppers [15,39,40], while capsanthin could be transformed into orange or yellow pigments in the process of photodegradation, such as zeaxanthin, lutein, β-carotene, and other carotenoid substances [41,42]. Moreover, the oxidative degradation process of yellow carotenoids is relatively slow [6].…”
Section: Color Traitsmentioning
confidence: 99%
“…However, studies in humans have shown that capsanthin, because of its high lipophilicity and poor solubility in gastrointestinal fluids has low and highly variable oral bioavailability. 7,8 Moreover, capsanthin is prone to oxidative degradation in the presence of heat, humidity, and light, 9,10 which can compromise its antioxidant activity to a great extent. 11 Thus, to fully harness the potential of capsanthin as a functional food and natural colorant, it is quite important to develop a commercially viable delivery system that can improve solubility, dissolution, and absorption of capsanthin without compromising its stability and antioxidant activity.…”
mentioning
confidence: 99%